Technology and Society Public Perception: A Structural Equation Modeling Study of the Brazilian Undergraduate Students’ Opinions and Attitudes from Sao Paulo State - Veraszto, Estéfano Vizconde; Camargo, José Tarcísio Franco de; Silva, Dirceu da; Freitas, Leandro Valim de (IntechOpen, 2013)
None